Specific training adjustments for young discus throwers as a prerequisite for achieving elite performanve - Vrcic, M.; Pavlovic, R.; Solakovic, S.; Kovaèevic, E.; Abazovic, E. (SportLogia, 2016)
The aim of this paper is to demonstrate a model of specific discus thrower training adjustments, as well as depicting the most important characteristics of achieving elite performance. The most important aspects of the training programme have been taken into account, specifically those applied by discus throwers who have achieved significant improvements in their season. The improvement is indicated in the result of 58, 34 m (within the year 2016) compared with the result of 47,72m achieved in 2015, with the disc weight of 1,5 kg in the category U 18, representing a significant difference of 10,62 m. The result was achieved at the European Athletic Championship in the youth category. The attained result is likewise a personal best, and has been achieved during the finals of European Championship as perceived.